Are We There Yet? Exploring the Impact of Translating Cognitive Tests for Dementia Using Mobile Technology in an Aging Population - Ruggeri, Kai; Maguire, Áine; Andrews, Jack L.; Martin, Eric; Menon, Shantanu (Frontiers in Aging Neuroscience, 2016)
This study examines implications of the expanded use of mobile platforms in testing cognitive function, and generates evidence on the impact utilizing mobile platforms for dementia screen. The Saint Louis University Mental State examination (SLUMS) was ported onto a computerized mobile application named the Cambridge University Pen to Digital Equivalence assessment (CUPDE). CUPDE was piloted and compared to the traditional pen and paper version, with a common comparator test for both groups. Sixty healthy participants (aged 50 to 79) completed both measurements. Differences were tested between overall outcomes, individual items, and relationship with the comparator. Significant differences in the overall scores between the two testing versions as well as within individual items were observed. Even when groups were matched by cognitive function and age, scores on SLUMS original version (M = 19.75, SD = 3) were significantly higher than those on CUPDE (M = 15.88, SD = 3.5), t (15) = 3.02, p < .01. Mobile platforms require the development of new normative standards, even when items can be directly translated. Furthermore, these must fit ageing populations with significant variance in familiarity with mobile technology. Greater understanding of the interplay and related mechanisms between auditory and visual systems, which are not well understood yet in the context of mobile technologies, is mandatory.